An Unusual Cause of Acute Hypercapneic Respiratory Failure - Wang, Janice (Libertas Academica, 2011)
We present a rare cause of hypercapneic respiratory failure through this case report of a 72-year-old man presenting with progressive dyspnea and dysphagia over two years. Hypercapneic respiratory failure was acute on chronic in nature without an obvious etiology. Extensive workup for intrinsic pulmonary disease and neurologic causes were negative. Laryngoscopy and diagnostic imaging confirmed the diagnosis of diffuse idiopathic skeletal hyperostosis, also known as DISH, as the cause of upper airway obstruction leading to hypercapneic respiratory failure.